KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN DASAN CERMEN, DESA AIK DAREK, KECAMATAN BATUKLIANG, KABUPATEN LOMBOK TENGAH - Laorah Istifadilah; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Dasan Cermen Hamlet, located in Central Lombok, West Nusa Tenggara, has a significant potential for diverse yard plant diversity. This study aims to analyze the level of yard plant species diversity in the area. The method used was direct observation of plants found in community yards. The data obtained were analyzed using the Shannon-Wiener Index (H). The results showed several plant species with varying numbers of individuals. The diversity index (H) value of 1.37 is categorized as moderate. This indicates that the yard plant community in Dasan Cermen Hamlet has a fairly stable ecosystem.